Experimental evaluation of an automotive air conditioning system with a variable speed compressor [electronic resource] - 375012 Syed Muzaffar Syed Mohamad (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2006